The effect of nitrogen fertilization and Fusarium culmorum inoculation on the biomarkers of oxidative stress in wheat flag leaves - Matić, Magdalena, biologinja (Array, 2021)
During cultivation, wheat is exposed to several abiotic and/or biotic stress conditions that may adversely impact the wheat yield and quality. The impact of abiotic stress caused by nitrogen deficiency and biotic stress caused by phytopathogenic fungus Fusarium culmorum on biomarkers of oxidative stress in the flag leaf of nine winter wheat varieties (Ficko, U-1, Galloper, BC Mandica, BC Opsesija, Ingenio, Isengrain, Felix, and Bezostaya-1) was analyzed in this study. Hydrogen peroxide concentration and lipid peroxidation level were measured as indicators of oxidative stress, while the antioxidant response was determined by measuring the concentration of phenolic compounds and activities of antioxidant enzymes. Wheat variety and nitrogen treatment had a significant effect on all examined biomarkers of oxidative stress in the flag leaf, while the impact of Fusarium treatment was less pronounced. The most significant impact on the measured stress biomarkers had a low nitrogen level, which mainly increased hydrogen peroxide concentration and lipid peroxidation level and decreased activities of antioxidant enzymes in most varieties. The obtained results were discussed and compared with the previous study in which biochemical analyzes were performed on the wheat spike. There was no significant strong correlation between flag leaf and spike response in the measured parameters, which, in addition to the variety-specific response, also indicates a tissue-specific antioxidant response.